2000
DOI: 10.1034/j.1399-3011.2000.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Two MSA 2 peptides that bind to human red blood cells are relevant to Plasmodium falciparum merozoite invasion

Abstract: Plasmodium falciparum merozoite membrane surface antigen 2 (MSA2) has been associated with the development of protective immunity against malaria. MSA2 antibodies were able to inhibit in vitro merozoite invasion. In our search for experimental evidence concerning the participation of MSA2 in merozoite invasion, 40 peptides were synthesized according to sequences reported for the CAMP and FC27 prototype Plasmodium strains. These peptides were purified, 125I-radiolabeled and tested for their ability to bind to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…These included two kinases (PFB0665w, a serine threonine kinase and PFB0815w, a calciumdependant proteine kinase), which are thought to be involved in the regulation of the cell cycle, and proteins recognized to play a key role during the infection, such as PFB0300c, the MSP2 antigen, and KAHRP. [12][13][14][15][16] We also observed that seven of the eight SERA antigens were upregulated between the ring stage and the schizont stage. These SERA antigens have been well characterized as putative vaccine candidates and are also thought to play a key role during the infection and are known to be differentially transcribed.…”
Section: Units)mentioning
confidence: 57%
“…These included two kinases (PFB0665w, a serine threonine kinase and PFB0815w, a calciumdependant proteine kinase), which are thought to be involved in the regulation of the cell cycle, and proteins recognized to play a key role during the infection, such as PFB0300c, the MSP2 antigen, and KAHRP. [12][13][14][15][16] We also observed that seven of the eight SERA antigens were upregulated between the ring stage and the schizont stage. These SERA antigens have been well characterized as putative vaccine candidates and are also thought to play a key role during the infection and are known to be differentially transcribed.…”
Section: Units)mentioning
confidence: 57%
“…45 The same occurs with other conserved HABPs such as AMA-1-derived 4325 and MSP-derived 4044. The biological functions that have been determined for these native conserved HABPs (i.e., host cell binding ability [34][35][36][37][38][39][40] ) and immunological characteristics such as an immunological code of silence could thus be equal to or very similar to those presented by native proteins, strongly supporting our approach aimed at working with 15-25-mer, chemically synthesized peptides as a logical and rational methodology for minimal subunit-based synthetic vaccine development. FIGURE 2.…”
Section: Native and Modified Habp 3d Structurementioning
confidence: 79%
“…It has also been shown the same peptide can be presented within the context of different alleles from the same HLA-DRβ1*molecules, as happens with the Myelin Basic Protein peptide (MBP [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]. This peptide has been seen to bind to HLA-DRβ5* 0101 and DRβ1*1501 molecules in 2 totally different functional registers [132].…”
Section: General Considerationsmentioning
confidence: 96%
“…falciparum's great genetic variability (as mentioned before). For the sake of brevity, this manuscript only shows how some of the most well-known MSP1 [95], EBA-175 [96], MSP2 [97], RESA [98], SERA [99] and AMA-1 [100] molecule HABPs were identified by using a previouslydescribed, specific, tailor-made methodology [95,96]. Fig.…”
Section: Molecular Approach To the Invasion Processmentioning
confidence: 99%